2016
DOI: 10.1088/0967-3334/37/10/1701
|View full text |Cite
|
Sign up to set email alerts
|

Validity of wrist worn accelerometers and comparability between hip and wrist placement sites in estimating physical activity behaviour in preschool children

Abstract: Wrist-worn accelerometers can increase compliance with wearing accelerometers, however, several large scale studies continue to use hip-worn accelerometers and it is unclear how comparable data is from the two sites. The study aims were: to investigate agreement between wrist-and hip-worn accelerometers and to determine the validity of Johansson et al cut-points for wrist worn accelerometers in preschool children.A sample of 32 preschool children (21 boys, 4.2 (0.5) years, BMI 16.6 (1.1)) were videoed wearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
4
20
1
Order By: Relevance
“…Therefore, further research to find ways to optimize wrist-based accelerometry for MVPA levels would be beneficial as compliance is increased at this location. 22 The cut points derived from the current study are comparable to some previously published for this age group. 23 used direct observation criterion methods similar to the current study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Therefore, further research to find ways to optimize wrist-based accelerometry for MVPA levels would be beneficial as compliance is increased at this location. 22 The cut points derived from the current study are comparable to some previously published for this age group. 23 used direct observation criterion methods similar to the current study.…”
Section: Discussionsupporting
confidence: 85%
“…These results indicate that a combination of accelerometer placements may be most accurate for estimating both PA and SB in the pre‐school age population, as SB and MVPA are important when measuring children's overall PA levels. Therefore, further research to find ways to optimize wrist‐based accelerometry for MVPA levels would be beneficial as compliance is increased at this location . The cut points derived from the current study are comparable to some previously published for this age group.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As mentioned, it could be questioned whether wearing the accelerometer on the wrist is suitable for preschool children. Research has looked at the difference between wearing a wrist and hip accelerometer on preschool children and one study in Scotland found that wrist-worn accelerometers provided a valid estimate of total physical activity, whereas hip-worn accelerometers showed a reasonable agreement to cut-points [68]. This was supported by a study in Stockholm, Sweden, which similarly monitored preschool children and found that wrist-worn accelerometers performed more accurately when assessing time spent in sedentary, light activity and MVPA, when compared to hip-worn accelerometers [69].…”
Section: Discussionmentioning
confidence: 99%